Experimental investigation on the phase equilibria in the system Sn–Zr (0–100 at.% Zr) by using "spot-technique" and DTA. (April 2021) - Samanta, Biswajit; Balakrishnan, S.; Ananthasivan, K.
Abstract: The solid-liquid equilibria in the system Sn–Zr were investigated experimentally by using the spot technique (thermo-optometry based technique) and differential thermal analysis. The liquidus in the composition range 0–80 at.% Zr was experimentally established. The solidus-liquidus in the composition range 80–100 at.% Zr and all other invariant equilibria have also been re-established. The temperature pertaining to the congruent melting η ↔ Liq at 2279 ± 5 K had been found to be 14 K higher than the value presented in a recent thermodynamic assessment. The temperature corresponding to the peritectic reaction η + Liq ↔ ZrSn2 was found to be 1449 ± 9 K. The temperatures pertaining to the two peritectoid reactions reported in the system η + β-Zr ↔ A15 and β-Zr + A15 ↔ α-Zr were redetermined and were found to be 1473 ± 5 K and 1234 ± 5 K respectively. These values differ from the earlier measurements significantly and are more precise. All these phases were characterized by X-ray diffraction (XRD). The experimental liquidus data obtained were found to be in good agreement with the values obtained by interpolating the phase boundaries suggested in a recent thermodynamic assessment. All the liquidus measurements have been carried out in home made Y2 O3 crucibles. The chemical compatibility of a zirconium rich alloy containing 75 at.% Zr with the crucible had also been examined by using Scanning Electron Microscopy along with Energy Dispersive X-ray Analysis. Our study indicates that Y2 O3 crucibles are compatible with Sn-75 at.% Zr alloy. The data reported in this study are more precise, reliable and supersede those reported earlier. Highlights: The liquidus in the composition range 25 to 100 at.% Zr had been experimentally determined for the first time. The measured values of the congruent melting transformation η ↔ Liq and the peritectic transformation η + Liq. ↔ ZrSn2 were redetermined to be 2279 ±5 K (60.2 ± 0.5 at.% Zr) & 1449 ± 9 K, respectively. Temperatures pertaining to the peritectoid transformation η + β-Zr ↔ A15 and β-Zr + A15 ↔ α-Zr were redetermined to be 1473 ± 5 K and 1234 ± 5 K respectively. The η-phase has been characterized by using XRD and was found to comprise hexagonal η1 (Zr5 Sn3.8 ) and η2 (Zr5 Sn3.2 ) phases at room temperature. SEM and EDAX investigations of the used alloy samples containing 75 at.% Zr, revealed that the molten alloy is chemically compatible with the crucible made out of Y2 O3 .